Impact of betacyanins on responses to ultraviolet radiation in Amaranthus tricolor L. Issue 1 (1st January 2020) - Adhikary, Dinesh; Forsyth, Jillian A.; Murch, Susan J.; Deyholos, Michael K.
ABSTRACT: Relatively little is known about the physiological significance of betalain pigments. To investigate a possible protective role for betalains (betacyanin), from UV-B irradiation, two cultivars of A. tricolor, Red-Leaf (RL) and Green-Leaf (GL) were obtained and VIGS method was used to produce isogenic derivatives of RL. Short-term responses to UV-B in the leaves were compared with and without detectable betalains. Following exposure, the red and green tissues showed similar decrease in photosynthetic capacity and in the increased production of UV-B stress markers including melatonin, flavonoids, phenolics, and PAL1 and RCD1 gene transcripts. Red tissues showed an increase in photosynthetic pigments under UV-B treatment, whereas the photosynthetic pigments and CAB1 and CAB2 gene transcripts decreased. The responses observed were similar for both high-betacyanin (RL) plants, and green plants (VIGS, GL), from which it was concluded that betacyanin does not have a UV-B protective role in amaranth leaves, under the experimental conditions.